Functions and activities of the Area Committee on Microbiology of the National Committee for Clinical Laboratory Standards. - Washington, J A (1991)
The Area Committee on Microbiology of the National Committee for Clinical Laboratory Standards has responsibility for the development of guidelines and standards in the field of clinical microbiology. Through the consensus process, representatives from government, industry, and professional societies have developed standards on antibacterial susceptibility testing (M2, M7, and M11), antimycobacterial susceptibility testing (M24), quality assurance on commercially prepared microbiological culture media (M22), evaluation of production lots of dehydrated Mueller-Hinton agar (M6), and preparation and testing of fetal bovine serum for use as cell culture growth supplement (M25) and guidelines on bactericidal tests (M26), protection of laboratory workers from infections transmitted by blood, body fluids, and tissue (M29), blood film examination for parasites (M15), and development of in vitro susceptibility testing criteria and quality control parameters (M23).